ISLAMIC ECONOMIC VALUES ANALYSIS OF THE EFFECT OF WAGES, INVESTMENT, AND ICOR ON EMPLOYMENT IN LAMPUNG PROVINCE - Muhammad Amir Faiz; Nurlaili Nurlaili; Yulistia Devi (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
Development planning is essentially determined by the ability to secure financing for the resources to be invested in order to achieve the desired level of growth and prosperity. ICOR is a comparative value that provides information on how much investment is needed to increase economic output. This study aims to analyze the values of Islamic economics and the influence of wages, investment, and ICOR on labor absorption in Lampung Province. Quantitative research is used to prove a theory, whether it be the influence or relationship of a variable. In this study, the researcher already had a problem to investigate, so the researcher tried to find the root cause of the problem. The results of this study indicate that the wage level variable has a positive and significant effect on labor absorption in Lampung Province for the period 2014-2023. The inflation variable has a positive and insignificant effect on labor absorption in Lampung Province for the period 2014-2023. The ICOR variable has a positive and insignificant effect on labor absorption in Lampung Province for the period 2014-2023. The variables of wage level, investment, and incremental capital output ratio (ICOR) simultaneously have no significant effect on labor absorption in Lampung Province for the period 2014-2023.